Privatization and economic performance - Bishop, M (Oxford University Press, 1994)
Eighteen papers, five previously published, examine what has been learned from the extensive program of privatization that the U.K. government has completed and consider what elements of privatization remain to be achieved. Papers focus on principles, problems, and priorities in privatization; privatization policies and public enterprise; case studies of the electric industry, British Airways, the water industry in England and Wales, gas regulation, British Steel, refuse collection, postal services, and railways; privatization and domestic consumers; ownership, regulation, and the labor party; the costs of privatization in the U.K. and France; popular capitalism; management buy-outs and privatization; facts, theory, and evidence of privatization and the labor market; and international organization and productive efficiency. Contributors are mainly economists. Bishop is with The Economist. Kay is at the London Business School. Mayer is at Warwick Business School. Index.